Webinar Introduction to Canva / Farizuwana Akma Zulkifle and Nur Ida Aniza Rusli - Zulkifle, Farizuwana Akma; Rusli, Nur Ida Aniza (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Introduction to Canva was organised by the College of Computing, Informatics and Media Studies UiTM Negeri Sembilan Kampus Kuala Pilah on December 20th, 2022. This webinar was attended by 85 students from the program Faculty of Applied Science and Academy of Islamic Contemporary Studies. Dr Anis Farihan, who is affiliated with Universiti Malaysia Pahang, has been asked to present at this webinar. The webinar has been conducted through Microsoft Team platform where student can join the session through online. However, some students attend physically during the webinar.